Juridical Analysis of Breach Of Faith On Credit Verbal Agreement (Case Studi District Court Number : 10/PDT/G/2014/PN.DPK) - Ninda Tri Astuti (Authentica: Private Law Journal, 2025)
Breach of Faith or term applies to the violation of moral duty if an agreement is violated. However, in the case of accounts payable, an oral agreement will make it easier to violate the agreement that has been made. So in this case how to prove in court and legal protection against default in an oral debt and credit agreement. The research method used is normative juridical with data support based on legal material laws and court decisions. Proof of a written agreement before the court does not have to be proven by a letter, but can present witnesses with other evidence such as recognition or proof of transfer or documents related to the implementation of the agreement. The form of legal protection in the event of default on a credit agreement made orally is in the form of preventive and repressive. Preventive protection has been given before there is an event or dispute. While repressive problems or disputes have arisen in advance.